Follicular lymphoma: treatment and prognostic factors - Luminari,Stefano (2012)
Follicular lymphoma is the second most frequent non-Hodgkin lymphoma accounting for about 10-20% of all lymphomas in western countries. The median age at diagnosis is 60 years old. The clinical presentation is usually characterized by asymptomatic peripheral adenopathy in cervical, axillary, inguinal and femoral regions. Treatment options for patients with naïve or recurrent follicular lymphoma are still controversial, ranging from a "watch and wait" policy to hematopoietic stem cell transplantation. More recently, the availability of rituximab has substantially changed follicular lymphoma therapeutic approaches to such an extent that R-Chemo is now the standard induction first-line treatment. This review provides a general overview of the state of the art in the management of follicular lymphoma and also, a brief description regarding the current prognostic tools available for treatment decisions.